A Critique on the Book Nargesi Abhari’s Divan Correction - Ali Jalali (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The publication of newly found ancient works, if done carefully and with scientific principles, will pave the way for research in various fields of knowledge, but if done carelessly, it itself becomes problematic and adds knots to the knots. The Nargesi Abhari's Divan Correction is one of these cases in which many misreadings have occurred and the literary researcher cannot benefit from it. The book editor has chosen recordings that sometimes ignores the weight of the prosody, which is one of the priorities of ancient Persian poetry, and sometimes sacrifices the meaning for the dubious recording and puts a meaningless choice in front of the audience. Sometimes spelling mistakes also prevent Nargesi poetry from being understood. The present article points out the weaknesses and errors of this correction and points out the need to revise it in another edition.